Regenerative Endodontic Procedures of Immature Permanent Premolars with Periapical Lesions: A Report of Two Cases Using Two Different Materials, 18-Month Follow-Up - Hong Van Le; Tuan Anh Nguyen; Thai Son Vu (Hindawi Limited, 2023)
Regenerative endodontic procedure is an emerging alternative to traditional therapies for immature teeth with necrotic pulp with or without periapical lesions. This innovative approach, also known as revitalization procedures, is aimed at enhancing canal wall thickness, stimulating root lengthening, and promoting apical closure. The regenerative endodontic procedures involve minimally invasive cleaning to preserve stem cells, stimulation of bleeding and clot formation within the canal, and the use of biomaterials to stimulate differentiation. This method is the first choice in biologically based treatments for immature permanent teeth. We present two successful clinical cases in which regenerative endodontic procedures were performed on permanent premolars with necrotic pulp with symptomatic apical periodontitis and chronic apical abscess due to dens evaginatus. The same procedure was employed for both cases, utilizing two differential materials: ProRoot MTA (Dentsply Tulsa Dental Specialities, USA) and Biodentine™ (Septodont, Saint-Maur-des-Fossés, France). Both cases exhibited positive clinical and radiographic outcomes after an 18-month follow-up period including periapical healing, increased dentin thickness, root lengthening, and apical closure.